Method of shock wave overpressure reconstruction - Guo, Y.; Han, Y.; Wang, L. (Combustion, explosion, and shock waves, 2015)
A method of shock wave overpressure reconstruction is presented, which allows overcoming the drawbacks of the previous approaches associated with the lack of shock wave velocity measurement points and the limitations of the empirical formula. An optimal design of the testing system is proposed. Based on the optimal system, the shock wave velocity field is inverted with the use of the generalized inversion theory, and the overpressure distribution is obtained. The inversion results are preferable to empirical results because the experimental data are confirmed in a limited area. Methods of overpressure computation and visualization are described.